Use of sandstone powder as a mineral additive for concrete. (20th October 2018) - He, Zhen; Hu, Lingling; Li, Yang; Hu, Jun; Shao, Yixin
Highlights: Potential use of sandstone powder as a mineral additive in concrete was explored, the optimal specific surface area was suggested. Alkali silica reaction of concrete with reactive sandstone aggregate was characterized by addition of sandstone powder as mineral additive. Abstract: The potential use of sandstone powder as a mineral additive to replace cement in concrete was studied. The effect of sandstone powder addition on compressive strength and alkali-silica reaction was investigated. The parameters included the specific surface area, the cement replacement ratio and the silica fume hybrid. It was found that the increase in specific surface area of sandstone powder could improve the strength gain. Although the addition of sandstone powder might reduce the compressive strength, the maximum reduction was less than 35% when 50% replacement of cement was employed. The hybrid of sandstone powder with 5% silica fume had demonstrated an effective way to enhance the strength. Because of the pozzolanic behavior, the sandstone powder can effectively reduce alkali silica reaction in concrete with reactive sandstone coarse aggregates. In case that sandstone is the only aggregate source and there is no supplementary cementitious material available in the area, the sandstone powder, ground sufficiently fine, can be used as partial replacement of cement to improve the durability of concrete.